SDF‐1 inhibits the dedifferentiation of islet β cells in hyperglycaemia by up‐regulating FoxO1 via binding to CXCR4. Issue 3 (21st December 2021) - Chen, Xiang‐Yu; Shi, Ying‐Xin; Huang, Ya‐Ping; Ding, Min; Shen, Qi‐ling; Li, Chun‐Jun; Lin, Jing‐Na
Abstract: Islet β cell dedifferentiation is one of the most important mechanisms in the occurrence and development of diabetes. We studied the possible effects of chemokine stromal cell‐derived factor‐1 (SDF‐1) in the dedifferentiation of islet β cells. It was noted that the number of dedifferentiated islet β cells and the expression of SDF‐1 in pancreatic tissues significantly increased with diabetes. In islet β cell experiments, inhibition of SDF‐1 expression resulted in an increase in the number of dedifferentiated cells, while overexpression of SDF‐1 resulted in a decrease. This seemed to be contradicted by the effect of diabetes on the expression of SDF‐1 in pancreatic tissue, but it was concluded that this may be related to the loss of SDF‐1 activity. SDF‐1 binds to CXCR4 to form a complex, which activates and phosphorylates AKT, subsequently increases the expression of forkhead box O1 (FOXO1), and inhibits the dedifferentiation of islet β cells. This suggests that SDF‐1 may be a novel target in the treatment of diabetes.